Effect of using Algorithm diagrams on the achievement of tenth-grade students in mathematics and their attitudes towards them in Hebron Governorate - Moghrabi, Nabeel Ameen (Journal of Educational and Psychological Sciences, 2021)
This research aimed at exploring the effect of using Algorithm diagrams on the achievement of tenth grade students in mathematics and their attitudes towards them. The research was administered on a sample of (119) tenth grade students in the schools of south Hebron. The sample was divided into a control group and an experimental. The experimental group learnt Statistics and probabilities through the Algorithm diagrams whereas the control group learnt the same unit using the traditional method. Furthermore, the study tools included the achievement test and the attitudes scale which were administered before and after the experimentation. The results revealed statistically significant differences on the post-achievement test due to the method of instruction while there were no statistically significant differences due to gender and the interaction between gender and method of instruction. Moreover, the results showed that there were no statistically significant differences in the attitudes of the students towards mathematics due to gender and the interaction between gender and method of instruction. The researcher offered a number of recommendations including using Algorithm diagrams to teach mathematics.
Keywords: Algorithm diagrams; achievement; attitudes; tenth grade